Memulai Usaha Coffee Shop di Era New Normal Covid-19: Kajian Antropologi tentang Kewirausahaan Mahasiswa di Kota Padang - Annisa Azarin (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
The outbreak of the Covid-19 virus pandemic at the beginning of 2020 has brought various bad impacts in the business world, one of which is the coffee beverage industry or coffee shop. Several studies state that the Large-Scale Social Restriction (PSBB) policy implemented by the Government to break the chain of the spread of Covid-19 has resulted in many coffee shop businesses experiencing a decline and even closing. However, in the era of the New Normal policy, the coffee beverage business seems to be growing rapidly and most of these coffee shop businesses involve young entrepreneurs, including students. This study aims to see what their motivations are in managing their business in the midst of the Covid-19 pandemic and how to adapt their activities while managing their business in the midst of this Covid-19 pandemic.